Articulações pedagógicas para estudantes com deficiência intelectual na educação profissional e tecnológica - Rodrigues, Vitória Parodes (2023)
The Nacional Politic of Special Education in the Perspective of anInclusiveEducation (2008), was an important milestone for the performanceof Special Education and the inclusive movement. Since it can guarantee the transversalityofthe special education from preschooler’s/kindergarten education to theacademiceducation. In global context, the inclusive practices have been thought anddiscussed.This search tries to answer the objectives of analysis, verify thepedagogicarticulations from the institution, this process happened on two ways. By interviewsand question writing. Those questions come to answer how happened theprocessofinclusion to students with Intellectual Disability in the Occupational and Technological Education. The data of the interview were recorded with authorizationfromtheparticipants, then were transcribed, and so on indexed in a bank of datainthedigital archive. As subjects of the study there were participating: teachers, technicianineducational topics and coordinator of the project. There were four femaleparticipantsand one male. Al of them are servers on the searched institution. Thetimeofactuation of those professionals in this school, goes from 11 to 35 years. Aslocusofthe search the Occupational and Technological Education, in a public institutiononthe central region of Rio Grande do Sul, Brazil. As analysis of datawasusedcategorical lines, in terms of discuss the objectives of the search. That showstheinclusion is a process, and goes per challenges. Some teachers look resistant todoadaptation, and some others looks for help to do it. The search shows inapositiveway the process of inclusion of students with intellectual disability at thesearchedinstitution, with pedagogic articulations, between Teaching Management, teachersand the Educational Topics Coordination (CAED), counting with the supp